Construction of Meaning, Power, and Information in Accounting Information Systems: A Postmodern Reading of Organizational Culture - Suwito, Candra; Leniwati, Driana (The International Journal of Accounting and Business Society, 2026)
Purpose — This paper seeks to explore how meaning, power, and information are constructed within accounting information systems (AIS) through a postmodern reading of organizational culture, particularly in conditions of organizational uncertainty. Design/methodology/approach — This study adopts a qualitative approach using a single case study in a state-owned enterprise (BUMN) operating in Indonesia’s logistics sector. Data were collected through in-depth interviews, observations, and document analysis involving five purposively selected informants engaged in inventory management and AIS usage. The analysis employs an interpretive thematic approach using a Foucauldian Discourse Analysis framework. Findings — The findings indicate that AIS operates as a discursive arena where meaning is constructed and power relations are reproduced through reporting practices, control mechanisms, and information legitimation. A culture of uncertainty avoidance encourages organizational actors to position AIS as a dominant source of truth, leading decision-making to prioritize stability and certainty over flexibility. Practical implications — The implementation of AIS should not be viewed solely as a technical system but must consider cultural and power dynamics within organizations. A critical and reflective approach is necessary to ensure that AIS supports not only efficiency but also equitable and context-sensitive decision-making. Originality/value — This paper contributes to the literature by providing a postmodern perspective on AIS within the context of a state-owned enterprise in a developing economy, highlighting how organizational culture and power relations shape system use and meaning construction